Exogenous Phosphocreatine Application in Elderly and Senile Patients Operated for Colorectal Cancer - V. N. Derbugov; A. L. Potapov; V. I. Potievskaya; Ya. M. Khmelevski (Общая реаниматология, 2017)
Objective: to evaluate the efficacy of exogenous phosphocreatine (EPCr) application in elderly and senile patients operated for colorectal cancer.Material and methods. 80 patients with routine perioperative management (Group 1) and 56 patients in whom routine perioperative management was supplemented with EPCr administration (Group 2). Postoperative morbidity and duration of hospitalization after surgery have been assessed in both groups.Results. Postoperative morbidity was lower in Group 2: 7.2% vs. 35% (P=0.001; OR=0.18; 95% CI: 0.07—0.49), mainly due to decreasing the incidence of acute coronary syndrome and anastomotic leakage. The duration of hospi% talization after surgery was lower in Group 2 as well.Conclusions. Application of EPCr might be an effective measure to decrease the postoperative morbidity in elderly and senile patients with colorectal cancer.